IMPACT OF TYPES OF ELECTROMAGNETIC RADIATION ON LIVING NATURE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
In our daily life we are exposed to electromagnetic radiation in a very wide range. In our century, these radiations are constantly increasing, and we do not always know how to protect ourselves from them and how they affect people and the rest of living nature. An attempt has been made to analyze the impact of emissions from a different frequency spectrum - from power supply with a frequency of 50 Hertz to high-frequency mobile communications with a frequency of up to 300 GHz. Studies in countries of Europe and the world were taken as a basis, and a study was made about the impact of these electromagnetic radiations in Central Northern Bulgaria and the Veliko Tarnovo region. It is shown how morbidity changes when they affect the peripheral and central nervous systems of people and what effect they can cause at high powers and high intensity at short distances.